An Automated Computer‐Vision "Bubble‐Counting" Technique to Characterise CO2 Dissolution into an Acetonitrile Flow Stream in a Teflon AF‐2400 Tube‐in‐Tube Flow Device. Issue 1 (12th December 2022) - O'Brien, Matthew; Moraru, Ruxandra
Abstract: Invited for this month′s cover is the group of Matt O'Brien at Keele University. The cover picture shows a depiction of 'computer vision' in the context of CO2 dissolution into tube‐in‐tube membrane devices in continuous flow. The original manuscript is part of the Special Collection on "Automation in Chemistry and Beyond" and more information can be found in the Research Article by Matthew O'Brien and Ruxandra Moraru . Abstract : A computer‐vision 'bubble counting' approach was used to estimate CO2 dissolution into acetonitrile in a Teflon AF‐2400 tube‐in‐tube device. The observed differences to our previously reported methodology (inline titration) can be accounted for if residual dissolved CO2 (that doesn't outgas) is taken into consideration. Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.202200167 ).